The Role of Aluminium Nitride as Reinforcement Material for Phase Change Materials (PCMS): A Review on Synthesis, Characterization and Applications in Thermal Energy Storage - I Kadek Ervan Hadi Wiryanta; Tjokorda Gde Tirta Nindhia; Wayan Nata Septiadi; I Made Joni (Logic : Jurnal Rancang Bangun dan Teknologi, 2025)
The improvement of thermal energy storage and management has become a significant focus in various industrial applications, including EV battery thermal management, solar energy storage, and high-power electronics. Phase Change Materials (PCM) are widely used for thermal energy storage due to their capacity to absorb and release latent heat. However, organic-based PCMs like paraffin have limited heat conductivity (~0.2 W/mK), limiting their efficiency. This research investigates the potential of Aluminum Nitride (AlN) as a reinforcing material to improve the thermal conductivity and stability of PCM composites. AlN has strong thermal conductivity (~300 W/mK), chemical stability, and oxidation resistance, making it a promising material for increasing PCM thermal performance. Several synthesis methods, including Carbothermal Reduction Nitridation (CRN), sol-gel, hydrothermal, and thermal plasma procedures, have been investigated to produce AlN nanoparticles with appropriate characteristics for integrating into PCM matrices. Furthermore, multiple dispersion strategies, including ultrasonication, surface functionalization, and surfactant-assisted dispersion, are studied to ensure uniform distribution and prevent sedimentation. The use of surfactants like Sodium Dodecyl Sulfate (SDS) and Sodium Stearoyl Lactylate (SSL) further improves dispersion and stability, preventing phase separation and maintaining long-term efficiency. In applications such as EV battery thermal management, AlN-enhanced PCMs demonstrate superior heat dissipation, reducing battery peak temperatures by 19.4% compared to conventional air-cooled systems. Further research is recommended to explore hybrid nanocomposites, optimize AlN particle size and morphology, and develop advanced dispersion techniques to maximize the efficiency of PCM-AlN composites.